Pengaruh Perhatian Orang Tua, Konsep Diri dan Aktivitas Belajar terhadap Prestasi Belajar Matematika: Penelitian Di SMP Kecamatan Cipondoh Kota Tangerang - Nur Alim Noor (LPPM STKIP Kusuma Negara, 2016)
The purpose of this study was to determine the effect of parental attention , self-concept , and learning activities together on learning achievement in Mathematics. Knowing the influence of parents' attention on learning achievement in Mathematics. Knowing the influence of self-concept on learning achievement in Mathematics. Knowing the effect of learning activities to learning achievement in Mathematics. The results showed a significant effect of parental attention , self-concept and learning activities besma together on learning achievement in Mathematics. This is evidenced by the numbers sig = 0.000 and 0.05 is far below the figure far above Fh = 54.468 Ftabel = 2.72. Figures show the influence 0,816 R regulation is quite high and the numbers R square 0,666. determination coefficient of 66.6 % . This means that the attention of parents , self-concept and learning activities together contributed 66.6% to the achievement of learning mathematics . While regression analysis yields the equation 0,033X ? = -5.393 + 0,082X2 0,107X3From these equations show any increase in the value of parental attention , then there will be increase in mathematics achievement at 0.033 . Any increase in the value of self-concept will be an increase learning achievement at 0.082 . And any increase in the value of the learning activities will be an increase mathematics achievement at 0.107 . More partial effect of each of the variables showed significant results on learning achievement in Mathematics. This is evidenced by the data table Coeficientsa where the results for the variable X1 digit figures Sig = 0.005 th = 2.874 . For variable Sig X2 = 0.000 and the numbers th = 4.447 . And for X3 numbers and figures Sig = 0.000 th = 6.038 . From these data showed the Sig of each variable is less than 0.05 . While the numbers of each variable thitung show greater than table = 1.67 .